2013
DOI: 10.1016/j.ijcard.2013.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhaled iloprost on the exercise function of Fontan patients: A demonstration of concept

Abstract: Background Exercise capacity following Fontan surgery is often depressed. An inability to reduce pulmonary vascular resistance appropriately during exercise may contribute to this phenomenon. The aim of this study was to determine whether administration of iloprost, a selective pulmonary vasodilator, would improve exercise function after Fontan procedure. Methods Double-blind, randomized, placebo controlled, crossover trial. Patients performed two cardiopulmonary exercise tests (CPX) separated by <1 month. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 30 publications
0
63
0
2
Order By: Relevance
“…Giardini et al 8 showed an improvement in peak oxygen consumption after a single oral dose of sildenafil, whereas Goldberg et al 9,10 observed an improvement in ventilatory efficiency and ventricular performance after a 6-week period of sildenafil therapy. Rhodes et al 35 noted a similar beneficial effect of inhaled iloprost on exercise capacity. The hemodynamic mechanisms for the improvement remained unclear.…”
Section: Effect Of Sildenafil On Exercise Hemodynamicsmentioning
confidence: 85%
“…Giardini et al 8 showed an improvement in peak oxygen consumption after a single oral dose of sildenafil, whereas Goldberg et al 9,10 observed an improvement in ventilatory efficiency and ventricular performance after a 6-week period of sildenafil therapy. Rhodes et al 35 noted a similar beneficial effect of inhaled iloprost on exercise capacity. The hemodynamic mechanisms for the improvement remained unclear.…”
Section: Effect Of Sildenafil On Exercise Hemodynamicsmentioning
confidence: 85%
“…. 23 From these observations with pulmonary vasodilators, it was anticipated that subgroup analyses in our study could pinpoint measures such as baseline peak…”
mentioning
confidence: 97%
“…A number of studies have demonstrated acute improvements in exercise performance, ejection fraction, and cardiac output, while the only reported randomized clinical trial showed improvements in some sub-groups during sub-maximal exercise, but did not detect an improvement in maximal oxygen consumption 1014 . More recently, investigators have evaluated the effect of Bosentan and inhaled prostacyclin on measures of exercise performance 2325 . The results of these studies were also mixed; one demonstrating a possible benefit and the other demonstrating no evidence of benefit.…”
Section: Discussionmentioning
confidence: 99%